2022
DOI: 10.1039/d1ra08092j
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization and cell labelling of strong pH-controlled bicolor fluorescence carbonized polymer dots

Abstract: Multicolor fluorescence N-doped CPDs from dextrin water solution in strong acidic and alkaline environments were synthesized and characterized, which revealed that pH value plays a vital role in the process of CPD growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…[1][2][3] In particular, CDs have the advantages of high biocompatibility, low toxicity, water-solubility, intense photoluminescence, photostability and cost-effective synthesis. 4,5 CDs typically have a small size (o10 nm) consisting of carbon, oxygen, and nitrogen atoms and can be prepared by top-down and bottom-up methods. 6 The bottom-up synthesis of CDs proceeds through carbonization and polymerization of small molecules, which are then assembled into CDs by chemical reactions, and is a common and preferable method due to the facile and green processes.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] In particular, CDs have the advantages of high biocompatibility, low toxicity, water-solubility, intense photoluminescence, photostability and cost-effective synthesis. 4,5 CDs typically have a small size (o10 nm) consisting of carbon, oxygen, and nitrogen atoms and can be prepared by top-down and bottom-up methods. 6 The bottom-up synthesis of CDs proceeds through carbonization and polymerization of small molecules, which are then assembled into CDs by chemical reactions, and is a common and preferable method due to the facile and green processes.…”
Section: Introductionmentioning
confidence: 99%
“…(A) Reproduced with permission. 106 Copyright 2022, Royal Society of Chemistry. (B) Reproduced with permission.…”
Section: Synthesis Conditionsmentioning
confidence: 99%
“…pH-Induced structure transformation is an effective strategy for achieving multicolor conversion and performance improvement of CDs. 105 Liu et al 106 reported CDs with two-color emission (blue and yellow) using a hydrothermal method to modulate the pH (strong acidic or alkaline) of dextrin water solution (Fig. 3A).…”
Section: Design Of Multicolor Emission Carbon Dotsmentioning
confidence: 99%